Characterisation of Biogenic Amines in Fish Collected from Sarawak Using Gas Chromatography - Muhammad Abdurrahman, Munir; Zaini, Assim; Fasihuddin, Badruddin Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Determination of five biogenic amines (heptylamine, histamine, tyramine, cadaverine and spermidine) in fish was optimised and validated using gas chromatography – flame ionisation detector (GC-FID) followed by confirmation using mass spectrometry (MS). The biogenic amines were derivatised using BSA (N, O-bis (trimethylsilyl) acetamide) + TMCS (trimethylchlorosilane) as a derivatisation agent. The linear working range was between 0.9995 – 0.9999. The limit of detection (LODs) were in the range of 1.20 – 2.90 μg/mL. The efficiency of recovery for every biogenic amines, which ranged between 98.41 – 116.39%, indicated that analytical procedure can be used to extract biogenic amines in fish. Using GC-FID, the concentration of five biogenic amines were simultaneously determined in fresh and salted fish samples such as mackerel (Scomberomorus guttatus), sardine (Sardinella gibbosa), whiptail (Himantura walga), gourami (Trichogaster pectoralis) and toli shad (Tenualosa toli). Histamine is found in fresh mackerel (S. guttatus) and sardine (S. gibbosa) at concentration of 5.96 and 2.69 mg/kg, respectively. Salted sardine (S. gibbosa) has histamine concentration of 8.95 mg/kg. All histamine concentrations detected were below 50 mg/kg (FDA regulation) which is below the permissible threshold associated with scombroid poisoning. Cadaverine was detected in fresh sardine (S. gibbosa), whiptail stingray (H. walga) and salted gourami (T. pectoralis) with concentration of 4.96, 146.39 and 18.80 mg/kg, respectively. None of them has biogenic amines, and histamine within FDA regulation levels (below 50 mg/kg).